Fyn Is Downstream of the HGF/MET Signaling Axis and Affects Cellular Shape and Tropism in PC3 Cells - Jensen, Ana R.; David, Saito Y.; Liao, Chuanhong; Dai, Jinlu; Keller, Evan T.; Al-Ahmadie, Hikmat; Dakin-Haché, Kelly; Usatyuk, Peter; Sievert, Margarit F.; Paner, Gladell P.; Yala, Soheil; Cervantes, Gustavo M.; et al. (Clinical cancer research, 2011)
Purpose: Fyn is a member of the Src family of kinases that we have previously shown to be overexpressed in prostate cancer. This study defines the biological impact of Fyn inhibition in cancer using a PC3 prostate cancer model. Experimental Design: Fyn expression was suppressed in PC3 cells using an shRNA against Fyn (PC3/FYN-). Knockdown cells were characterized using standard growth curves and time-lapse video microscopy of wound assays and Dunn Chamber assays. Tissue microarray analysis was used to verify the physiologic relevance of the HGF/MET axis in human samples. Flank injections of nude mice were performed to assess in vivo growth characteristics. Results: HGF was found to be sufficient to drive Fyn-mediated events. Compared to control transductants (PC3/Ctrl), PC3/FYN- showed a 21% decrease in growth at 4 days (P = 0.05). PC3/FYN- cells were 34% longer than control cells (P = 0.018) with 50% increase in overall surface area (P < 0.001). Furthermore, when placed in a gradient of HGF, PC3/FYN- cells showed impaired directed chemotaxis down an HGF gradient in comparison to PC3/Ctrl (P = 0.001) despite a 41% increase in cellular movement speed. In vivo studies showed 66% difference of PC3/FYN- cell growth at 8 weeks using bidimensional measurements (P = 0.002). Conclusions: Fyn plays an important role in prostate cancer biology by facilitating cellular growth and by regulating directed chemotaxis—a key component of metastasis. This finding bears particular translational importance when studying the effect of Fyn inhibition in human subjects. Clin Cancer Res; 17(10); 3112–22. ©2011 AACR.